Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3389/fmicb.2018.01921
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbiota Transplantation Ameliorates Experimentally Induced Colitis in Mice by Upregulating AhR

Abstract: Ulcerative colitis (UC) is a chronic non-specific inflammatory disease that occurs in the colon and rectum. While fecal microbiota transplantation (FMT) is gaining attention as a clinical treatment of UC, the molecular mechanisms behind this effect have yet to be fully understood. A C57BL/6 mouse model was established to test whether FMT promotes the recovery of colon inflammation. Administration of 2% dextran sulfate sodium (DSS) for 7 days successfully induced acute colitis, as evidenced by diarrhea, hematoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 44 publications
4
39
2
Order By: Relevance
“…Recently, experimental evidence has linked the effectiveness of FMT for colitis with immunosuppression. FMT therapeutically controlled gut inflammation and colitis via the induction of IL-10 and TGF-β, cytokines critical for Treg cell accumulation in the intestine [67,68]. Whether FMT-directed immunosuppression aids in the recovery from C. difficile requires further investigation.…”
Section: Certain Microbes Can Elicit Immunosuppression After Colonizamentioning
confidence: 99%
“…Recently, experimental evidence has linked the effectiveness of FMT for colitis with immunosuppression. FMT therapeutically controlled gut inflammation and colitis via the induction of IL-10 and TGF-β, cytokines critical for Treg cell accumulation in the intestine [67,68]. Whether FMT-directed immunosuppression aids in the recovery from C. difficile requires further investigation.…”
Section: Certain Microbes Can Elicit Immunosuppression After Colonizamentioning
confidence: 99%
“…In a separate study, FMT was shown to up-regulate the expression of aryl hydrocarbon receptor (AhR), IL-10 and TGF-β in colon tissues in mice with DSS-induced colitis and was associated with improvement in the severity of colon mucosa injury and histological parameters [102]. This correlated with gut microbial recovery of Lactobacillus and Bifidobacterium species and an increase in tryptophan levels which, as demonstrated by this study, results in differentiation of immune cells in order to promote or regulate the release of anti-inflammatory factors [103][104][105].…”
Section: Immunological Mechanistic Insights For Fmt In Ibd Using Animmentioning
confidence: 99%
“…Restoring a main ecology of normal organisms contributed to resolving inflammation (Burrello et al, 2019). Wei et al (2018) identified that FMT could alleviate the acute colitis stimulated by DSS in mice and FMT results in the upregulation of not only aryl hydrocarbon receptor (AHR) but also transforming growth factor beta (TGF-b) and IL-10 in colon tissues. Wang et al (2020) carried out a study on active UC patients who received three times FMT from a single donor at an interval of 2-3 months.…”
Section: Inflammatory Cytokinesmentioning
confidence: 99%